The Role of Digital Literacy in Teaching the Islamic Education - Shofiyah, Luthfi Nurul (Universitas Muhammadiyah Surakarta, 2023)
This study aims to describe efforts to determine the role of digital literacy in learning Islamic Religious Education in MAN 2 Surakarta. This research method uses a qualitative approach, which is sourced from primary data. The primary data source was obtained from an interview with one of the teachers of PAI MAN 2 Surakarta subjects related to digital literacy in the learning process of Islamic Religious Education at MAN 2 Surakarta. The results of this interview show that MAN 2surakarta students utilize CBT E-Learning y through which can be accessed via YouTube, Digital literacy as a learning tool that invites students to explore and develop learning materials using website-based learning media. From the results of interviews regarding digital competency frameworks. The framework consists of a set of skills that teachers and students have when using and utilizing digital-based learning tools.